(3cJGH GdeYQGLs - (3CHh GdbGSe YHO GdcQje GdbTjQj,J (B465 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eDjO GdOjf hfGUQg hehVM GdMb HHUGFQg heQSd GdCfHjGA HCMcGeg aUd GdeYQGL ai GddZI GdSde hLeYg eYGQjL s
(3BNQgG (B:s
(3agPG WQa ef GdcdGe ai gPg GdBjGJ ef ShQI hGdfLe hPcQfGgG dJYdbgG HGdeYQGL hHgPG jfJgi GdcdGe ai GdeYQGL hHGddg GdJhajb hdG Mhd hdGbhI EdG HGddg GdYdi GdYXje Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3WGdYg hUMMg CMeO Hf eMeO Hf CMeO Hf YHO GdhgGH GdMSfi GdMSjfi GdeUQis
(3gi GdfSNI GdhMjOI Ydi eG jPcQ HQhcdeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1460s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs